Keberterimaan Situs Pajak: Pengindusian Orientasi Tujuan Pembelajaran dan Norma Subyektif - ., Sumiyana; Pribadi, Angelia (Jurnal Akuntansi Multiparadigma, 2010)
This study investigates a new IS success model that predicts the net benefits of tax consultansâ works especially in Indonesia by inducing learning goal orientation and subjective norms. This research investigates initially the basic IS success model (DeLone dan McLean, 1992) using system quality, information quality, intention to use and net benefits. This study induces stepwisely learning goal orientation and subjective norms to this model to predict net benefits improvement of the IS success model. This study suggests that system quality and information quality enhance intention to use and usersâ satisfaction, then they could make net benefits. This study finds low goodness of fit level of the basic model. The inducement of learning goal orientation to the basic model did not improve the level, neither did subjective norms. It means that tax information systems in Indonesia are still far from the IS that could be used as decision support systems or expert systems tools.